The Role Of Clinic Instructors As Motivators With Student Readiness To Care For Covid-19 Patients - Maria Agustina Ermi Tri Sulistiyowati; Maria Suryani; Johanita Ela Cornalia; Agnes Cecila Sagala (Jurnal Smart Keperawatan, 2023)
The Covid-19 pandemic is still ongoing. When nursing students carry out clinical practice, they have the possibility to treat patients with Covid-19. Clinical supervisors as people closest to students have a role as a motivator to motivate students to be ready to treat Covid-19 patients. The aim is to find out the role of the clinical supervisor as a motivator with the readiness of students to treat Covid-19 patients. Analytical descriptive design, with a cross sectional approach. Population of nursing student Elisabeth College of Health Sciences Semarang. A sample of 170 people was taken by total sampling technique. The data was tested using the Kolmogorov Smirnov test. Most of the respondents (85.9%) rated the role of the clinical supervisor as a motivator in the good category and as many as 156 respondents (91.8%) had high readiness to treat Covid 19 patients. The Kolmogorov Smirnov test results obtained a p value of 1,000, there was no relationship the role of the supervisor as a motivator with readiness to care for Covid 19 patients. It is recommended that students remain vigilant and implement health protocols while carrying out clinical nursing practice Keywords: readiness to treat Covid-19 patients; motivator; clinical supervisor rolePeran Instruktur Klinik Sebagai Motivator Dengan Kesiapan Mahasiswa Untuk Perawatan Pasien Covid-19ABSTRAK  Pandemi Covid-19 sampai saat ini masih berlangsung. Pada saat mahasiswa keperawatan melaksanakan praktik klinik, mereka memiliki kemungkinan untuk merawat pasien dengan Covid-19. Pembimbing klinik sebagai orang yang terdekat dengan mahasiswa memiliki peran sebagai motivator untuk memotivasi mahasiswa agar siap merawat pasien covid-19. Tujuan untuk mengetahui peran pembimbing klinik sebagai motivator dengan kesiapan mahasiswa merawat pasien Covid-19. Desain  deskriptif analitik, dengan pendekatan cross sectional. Populasi mahasiswa keperawatan Sekolah Tinggi Ilmu Kesehatan Elisabeth Semarang. Sampel sebanyak 170 orang diambil dengan teknik total sampling. Data diuji menggunakan uji Kolmogorov Smirnov. Sebagian besar responden (85,9%)  menilai peran pembimbing klinik sebagai motivator dalam kategori baik dan sebanyak 156 responden (91,8%) memiliki kesiapan tinggi untuk merawat pasien Covid 19. Hasil uji Kolmogorov Smirnov didapatkan nilai p value 1,000, tidak ada hubungan peran pembimbing sebagai motivator dengan kesiapan merawat pasien Covid 19. Disarankan mahasiswa tetap waspada dan menerapkan protokol kesehatan selama menjalankan praktik klinik keperawatan Kata kunci : kesiapan merawat pasien Covid-19; motivator; peran pembimbing klinik